2015
DOI: 10.25149/1756-8358.1102013
|View full text |Cite
|
Sign up to set email alerts
|

Treating Anxiety with either Beta Blockers or Antiemetic Antimuscarinic Drugs: A Review

Abstract: Beta adrenergic receptor antagonists and antiemetic muscarinic receptor antagonists are useful for mental health in primary care and family medicine settings, as they provide favorable risk/benefit profiles, and especially so relative to benzodiazepines. Beta blockers (e.g., propranolol) prescribed off-label have been known for decades to provide some, albeit limited, anxiolytic benefit for patients affected by social anxiety disorder (social phobia), including performance anxiety. Blockage of adrenaline's bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 91 publications
(95 reference statements)
1
32
0
2
Order By: Relevance
“…Findings revealed that PRO failed to influence anxiety or cognitive performance. This negative finding could be due to insufficient dose amount (40 mg single dose) (Dooley 2015) or time of administration (90 min prior to task) (Müller et al 2005), or it could be specific to the experimental design, i.e., PRO has no effect on anxiety induced by threat of shock.…”
Section: Discussionmentioning
confidence: 99%
“…Findings revealed that PRO failed to influence anxiety or cognitive performance. This negative finding could be due to insufficient dose amount (40 mg single dose) (Dooley 2015) or time of administration (90 min prior to task) (Müller et al 2005), or it could be specific to the experimental design, i.e., PRO has no effect on anxiety induced by threat of shock.…”
Section: Discussionmentioning
confidence: 99%
“…This paper initiated a debate on pharmacotherapy using beta blockers in hypertension, which continues until today. Later, research was conducted which demonstrated that beta blockers are a safe therapeutic option in treating arrhythmia and chronic congestive heart failure [29].…”
Section: Pharmacological Properties and The Spectrum Of Clinical Applmentioning
confidence: 99%
“…Praca zainicjowała dyskusję nad tematem farmakoterapii z zastosowaniem adrenolityków typu beta w nadciśnieniu, która trwa do chwili obecnej. W późniejszym czasie wykonano badania, z których wynikało, iż betaadrenolityki są bezpieczną opcją terapeutyczną w leczeniu arytmii serca oraz przewlekłej, zastoinowej niewydolności serca [29].…”
Section: Właściwości Farmakologiczne I Spektrum Kliniczne Zastosowaniunclassified
“…β-blockers have been used as drugs for more than 50 years in the therapy of several diseases of the cardiovascular system [1] as well as in other disorders connected with an increase in sympathetic tone, such as glaucoma [2,3], anxiety [4], thyrotoxicosis [5], osteoporosis [6], and migraine prophylaxis [7]. The study of this drug group is substantiated by high incidence rate of cardiovascular diseases [8], such as ischemic heart disease, hypertension [9][10][11][12], heart arrhythmia, hypertrophic cardiomyopathy [13], and heart failure [8,14], all of which have been brought into connection with β-adrenergic receptors.…”
Section: Introductionmentioning
confidence: 99%